MOLLUSCICIDAL ACTIVITY OF ZINGIBER OFFICINALE AND CARICA PAPAYA ON THE EGG HATCHABILITY OF THE GOLDEN APPLE SNAIL, POMACEA CANALICULATA (GASTROPODA: AMPULIRIIDAE) - Ismail, Hasnun Nita; Musa, Nadia Nisha (Malaysian Journal of Science, 2021)
The study was conducted to assess the effect of Zingiber officinale and Carica papaya extract on the egg hatchability of the golden apple snail, Pomacea canaliculata. This is a freshwater snail that is considered a pest in agriculture as well as natural ecosystems. In combating the population of the aforementioned pest, this study evaluates the use of plant extracts such as biomolluscicides to control the production of new hatchlings from the clusters of eggs. The egg clusters were exposed to different concentrations of Z. officinale ethanolic extract and C. papaya methanolic extracts (25 ppm, 50 ppm, 100 ppm) using the direct single spraying method. Observation was made for a maximum of 30 days. The time taken for the eggs to hatch and the number of eggs successfully hatched were measured to reflect the potential of both extracts in affecting egg hatchability. The finding shows that the eggs hatch later when exposed to increasing concentrations (25 to 100 ppm) of Z. officinale extract. The number of eggs successfully hatched was significantly decreased from 86% to 9% after exposure to 25 ppm and above. Meanwhile, the extract of C. papaya did not show any significant effect on both parameters for egg hatchability of P. canaliculata, regardless of the increase in concentration from 25 to 100 ppm. Our findings reveal that the extract of Z. officinale contains higher molluscicidal activity than the extract of C. papaya. Therefore, it has the potential to be commercialized as a biomolluscicide to control the population of golden apple snails specifically at the egg stage.